Bi-layered calcium phosphate cement-based composite scaffold mimicking natural bone structure - He, Fupo; Ye, Jiandong (Science and technology of advanced materials, 2013)
In this study, a core/shell bi-layered calcium phosphate cement (CPC)-based composite scaffold with adjustable compressive strength, which mimicked the structure of natural cortical/cancellous bone, was fabricated. The dense tubular CPC shell was prepared by isostatic pressing CPC powder with a specially designed mould. A porous CPC core with unidirectional lamellar pore structure was fabricated inside the cavity of dense tubular CPC shell by unidirectional freeze casting, followed by infiltration of poly(lactic-co-glycolic acid) and immobilization of collagen. The compressive strength of bi-layered CPC-based composite scaffold can be controlled by varying thickness ratio of dense layer to porous layer. Compared to the scaffold without dense shell, the pore interconnection of bi-layered scaffold was not obviously compromised because of its high unidirectional interconnectivity but poor three dimensional interconnectivity. The in vitro results showed that the rat bone marrow stromal cells attached and proliferated well on the bi-layered CPC-based composite scaffold. This novel bi-layered CPC-based composite scaffold is promising for bone repair.